Elbasvir/grazoprevir in women with hepatitis C virus infection taking oral contraceptives or hormone replacement therapy - Hézode C; Kwo P; Sperl J; Hwang P; Long J; Talwani R; Robertson MN; Haber BA (Dove Medical Press, 2019)
Christophe Hézode,1 Paul Kwo,2 Jan Sperl,3 Peggy Hwang,4 Jianmin Long,4 Rohit Talwani,4 Michael N Robertson,4 Barbara A Haber4 1Service d’Hépatologie, Hôpital Henri-Mondor, AP-HP, Université Paris-Est, INSERM U955, Créteil, France; 2Division of Gastroenterology/Hepatology, Department of Medicine, Stanford University School of Medicine, Palo Alto, CA, USA; 3Department of Hepatogastroenterology, Institut Klinické a Experimentální Medicíny (IKEM), Prague, Czech Republic; 4Department of Infectious Disease, Merck & Co., Inc., Kenilworth, NJ, USACorrespondence: Christophe HézodeService d’Hepatologie, Hôpital Henri Mondor, 51, avenue du Maréchal de Lattre de Tassigny, Créteil 94010, FranceTel +33 14 981 2111Email christophe.hezode@aphp.frIntroduction: Some direct-acting antiviral regimens for hepatitis C virus (HCV) infection pose safety or efficacy concerns if coadministered with drugs containing ethinyl estradiol. The present analysis was conducted to examine the impact of concomitant oral contraceptive pills (OCP) or hormone replacement therapy (HRT) during treatment with elbasvir (EBR)/grazoprevir (GZR) in women with HCV genotype (GT)1 or GT4 infection.Methods: This is a post hoc, integrated retrospective analysis of female participants with HCV GT1 or GT4 infection who received EBR 50 mg/GZR 100 mg once daily for 12 weeks in phase 2/3 clinical trials. The primary end point was sustained virologic response at 12 weeks after therapy completion (SVR12). For this analysis, participants were stratified according to whether they received OCP or HRT during the original treatment study.Results: A total of 1,022 women with HCV GT1 or GT4 infection were included (receiving OCP/HRT, n=81; not receiving OCP/HRT, n=941). Most participants receiving OCP/HRT were treatment-naive (79%), noncirrhotic (91.4%), and aged >35 years (71.6%). SVR12 rates were similar in women receiving OCP/HRT and those not receiving OCP/HRT (95.1% vs 96.3%). SVR12 rates remained high across all subgroups within the population receiving OCP/HRT: SVR12 rates were 94.6%, 100%, and 100% in participants with GT1a, GT1b, and GT4 infection, and all women aged 18–35 years achieved SVR (21/21). Treatment-related adverse events occurred in 40.7% (33/81) and 30.1% (283/941) of women receiving and those not receiving OCP/HRT, respectively.Conclusion: The efficacy and safety of EBR/GZR administered for 12 weeks was similar in women receiving OCP/HRT and those not on OCP/HRT. These data indicate that EBR/GZR can be safely used for the treatment of HCV GT1 or GT4 infection in women receiving concomitant OCP/HRT.Keywords: clinical trial, ethinyl estradiol, levonorgestrel, NS5A inhibitor, NS3/4A protease inhibitor